Fabrication and characterization of novel polyurethane Encapsulant with excellent underwater acoustic transparency and hydrophobicity. Issue 9 (5th July 2022) - Li, Zhihua; Zhang, Yidan; Yan, Shuxuan; Zhang, Yibo; Liu, Mengmei; Gong, Liangjun
Abstract: The preparation of underwater acoustically transparent polyurethane with excellent acoustic transparency, hydrophobicity, and electrical insulation is the current bottleneck prior in the underwater acoustic system. In this work, we synthesized a series of acoustically transparent polybutadiene‐based polyurethane (FPU) modified with a, ω‐dihydroxypoly[(3, 3, 3‐trifluoropropyl)methylsiloxane] (PTFPMS) by prepolymerization method. The influence of the PTFPMS content on the hydrophobicity, acoustic transparency, electrical insulation, and mechanical properties of FPU were investigated. When the amount of PTFPMS was 10 wt%, the water absorption of FPU reached the minimum of 0.261%, which was 42.9% lower than that of neat polyurethane. Moreover, the acoustic impedance of FPU decreased to 1.584 × 10 5  g/cm 2 ∙s, which was very close to that of seawater and indicated a favorable acoustic transparency. In addition, the volume resistivity and surface resistivity of FPU were 5.20 × 10 14  Ω cm and 2.42 × 10 14  Ω cm, respectively, suggesting an excellent electrical insulation. These results revealed that the as‐prepared FPU has promising applications in the fields of underwater acoustically transparent encapsulant. Abstract : In our work, polybutadiene‐based polyurethane modified with a, ω‐dihydroxypoly[(3, 3, 3‐trifluoropropyl)methylsiloxane] exhibited not only excellent underwater acoustic transparency, but also superior hydrophobicity.